2021
DOI: 10.1038/s41586-021-03306-8
|View full text |Cite
|
Sign up to set email alerts
|

A trade-off between plant and soil carbon storage under elevated CO2

Abstract: Terrestrial ecosystems remove about 30% of the CO 2 emitted by human activities each year 1 , yet the persistence of this carbon sink partly depends on how plant biomass and soil carbon stocks respond to future increases in atmospheric CO 2 2,3 . While plant biomass often increases in elevated CO 2 (eCO 2 ) experiments 4-6 , soil carbon has been observed to increase, remain unchanged, or even decline 7 . The mechanisms driving this variation across experiments remain poorly understood, creating uncertainty in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
221
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 361 publications
(268 citation statements)
references
References 82 publications
(98 reference statements)
9
221
1
Order By: Relevance
“…Belowground interactions that affect C storage in soils have been a major research interest in the past decades. Contrary to expectations of proportionality of aboveground biomass and soil C storage, a recent meta-review found that experimental effects of elevated CO 2 concentrations on soil carbon storage are inversely proportional to their effects on aboveground biomass (Terrer et al 2021). Positive effects on soil C were found in nutrientlimited situations with small aboveground biomass responses.…”
Section: Current State Of the Artmentioning
confidence: 77%
“…Belowground interactions that affect C storage in soils have been a major research interest in the past decades. Contrary to expectations of proportionality of aboveground biomass and soil C storage, a recent meta-review found that experimental effects of elevated CO 2 concentrations on soil carbon storage are inversely proportional to their effects on aboveground biomass (Terrer et al 2021). Positive effects on soil C were found in nutrientlimited situations with small aboveground biomass responses.…”
Section: Current State Of the Artmentioning
confidence: 77%
“…A potential problem with adaptation of forest management to increase soil C stocks is the possibility that a substantial part of the accumulated soil C stock may be lost after clear-felling (James and Harrison 2016;Nave et al 2010). Soil temperature and moisture are key factors controlling decomposition rates (Swift et al 1979), and clear-felling influence both (Jansson 1987), with a risk of destabilization of soil C. Below-ground C stocks also depend on plantsoil feedbacks and are expected to be sensitive to the removal of mycorrhizal trees at harvest (Kyaschenko et al 2017a). However, whether loss of mycorrhizal activity stabilize or destabilize the organic matter, remains unresolved (Frey 2019;Sterkenburg et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Some can secrete organic molecules from which plants gain resources for their growth directly [54]. For example, plants could use organic carbon as a carbon source [55]; moreover, they could absorb urea derivatives such as N-benzyl-N-isopropyl-N - [4-(trifluoromethoxy)phenyl]urea to supplement their nitrogen store [56]. Additionally, as signal molecules, some molecular organics (such as polyamines, phenolic acid, linolenic acid, etc.)…”
Section: Discussionmentioning
confidence: 99%